2022
DOI: 10.3389/fncel.2022.856124
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Hearing Impairment From Ambient Air Pollution and the Moderating Effect of a Healthy Diet: Findings From the United Kingdom Biobank

Abstract: The link between hearing impairment and air pollution has not been established, and the moderating effect of a healthy diet has never been investigated before. The purpose of this study was to investigate the association between air pollution and hearing impairment in British adults aged 37–73 years, and whether the association was modified by a healthy diet. We performed a cross-sectional population-based study with 158,811 participants who provided data from United Kingdom Biobank. A multivariate logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Additionally, the relationship between HL and certain types of air pollutants has been explored. Some studies have shown that environmental pollutants like PM 10 , NO 2 , CO, and SO 2 can adversely affect hearing 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the relationship between HL and certain types of air pollutants has been explored. Some studies have shown that environmental pollutants like PM 10 , NO 2 , CO, and SO 2 can adversely affect hearing 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%